Bali dalam Dinamika Masyarakat dan Kebudayaan di Tengah Perkembangan Pariwisata - I Made Pasek Subawa (UHN IGB Sugriwa Denpasar, 2018)
Culture inspired by the teachings of Hindu Religion is a big icon of pariwista in Bali. Can not be denied, that Bali is carrying on progress currently owned is due to the tourism system. With the rapid development of tourism, great effects also arise, both in the realm of economic culture or spiritual economics. This is what needs to be a common concern about how Bali looks ahead to tourism. In order for a culture system that is imbued by Hindu religious elements to show religious values that have not been inspired to the world, that Balinese culture can inspire the world.